Energy medicine East and West : a natural history of qi - Mayor, David F.; Micozzi, Marc S., 1953-; ScienceDirect eBooks (Edinburgh : Elsevier, 2011)
Energy Medicine East and West: A Natural History of Qi provides a unique, comprehensive overview of Qi or bioenergy for students and practitioners of energy medicines, Chinese and Oriental Medicine, and all disciplines of Complementary and Integrative Medicine. Mayor and Micozzi start with a comparative historical account of the ancient concepts of Qi and vital energy before covering theories of Qi, a discussion of the organized therapeutic modalities based upon Qi and its applications to specific health and medical conditions. Contributions are included from international experts in the field. The book moves from anatomical and bioenergetic complementarity of Western vital energy and Eastern Qi, through convergence of perspectives and models to demonstrations of how the traditional therapies are being melded together in a new, original and creative synthesis. David Mayor and Marc Micozzi are experienced medical practitioners, authors and editors. David Mayor has been actively involved in bioenergy research, practice and publishing for over 30 years, and is author/editor of Electroacupuncture: A practical manual and resource (2007), as well as other acupuncture texts and studies. Marc Micozzi is Professor in the Department of Physiology and Biophysics at Georgetown University School of Medicine, Washington, DC. As author/editor of Fundamentals of Complementary & Alternative Medicine, 4E (2011), and 25 other books, he has been writing, editing and teaching on bioenergy, Qi and related topics for 20 years.
Qigong, taiji quan (tai chi) and HIV : the psychoneuroimmunology connection / Mary Lou Galantino and Laura Muscatello -- Energy-based therapies in neurology : the example of therapeutic touch / Eric Leskowitz -- Qi in chronic fatigue and fibromyalgia / Carolyn McMakin and Peter H. Fraser -- The electrical heart : energy in cardiac health and disease / Alan Watkins -- Themes of qi and a dozen definitions : content analysis and discussion / David Mayor and Marc S. Micozzi.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Qi gong; Mind and body therapies; Mind and body therapies; Qi gong; Mind-Body Therapies -- methods; Qi; Mind-Body Relations, Metaphysical; Electronic books